2016
DOI: 10.3945/ajcn.115.127423
|View full text |Cite
|
Sign up to set email alerts
|

Spot urine sodium measurements do not accurately estimate dietary sodium intake in chronic kidney disease 1,2

Abstract: Background: Sodium intake influences blood pressure and proteinuria, yet the impact on long-term outcomes is uncertain in chronic kidney disease (CKD). Accurate assessment is essential for clinical and public policy recommendations, but few large-scale studies use 24-h urine collections. Recent studies that used spot urine sodium and associated estimating equations suggest that they may provide a suitable alternative, but their accuracy in patients with CKD is unknown. Objective: We compared the accuracy of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
(46 reference statements)
3
41
1
Order By: Relevance
“…Although the Tanaka formula showed the best performance in predicting 24-hUNa excretion at population level, the misclassification rates at individual level were more than 60%. These results were consistent with previous studies conducted in Chinese [17,20] and in US adults with chronic kidney disease [25]. It indicated that these six formulas might be inappropriate to estimate 24-hUNa excretion at individual level.…”
Section: Discussionsupporting
confidence: 91%
“…Although the Tanaka formula showed the best performance in predicting 24-hUNa excretion at population level, the misclassification rates at individual level were more than 60%. These results were consistent with previous studies conducted in Chinese [17,20] and in US adults with chronic kidney disease [25]. It indicated that these six formulas might be inappropriate to estimate 24-hUNa excretion at individual level.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, when participants were further classified into different salt intake groups on the basis of their estimated urinary sodium by the 3 estimation methods, .60% individuals were misclassified. This finding was consistent with a current validation study conducted in US adults with chronic kidney disease, which reported that only 18-50% of individuals were appropriately classified into their quartiles (25). Our work presented here suggests that existing methods for estimating 24-h sodium excretion commonly used in clinical and epidemiologic studies produce a high degree of variability and thus may lead to salt intake misclassification, which could contribute to null findings for the relation between salt intake and health outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…Estimation of 24-h urine sodium excretion from spot urine in patients with stage 3-4 chronic renal failure is not accurate. (9) Patients with a serum creatinine level ³2.0 mg/dl and those taking diuretics were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%